Training load and its progression from amateur to semi-professional rugby. - Al-Attar, J. J.; Croft, H.; Bloxham, K.; Blair, M. R. (Journal of Australian Strength and Conditioning, 2020)
Measuring and monitoring training load are necessary tools required for planning training sessions. This study monitored the training load (TL) of Rugby Union players as they transitioned from an amateur (club) into a semi-professional (Mitre-10 Cup) rugby environment. It also compared the changes in key global positioning system (GPS) metrics. Sixteen male players were monitored over three phases: Phase 1 (Club - weeks 1-3; Amateur), Phase 2 (Club & Mitre-10 Cup - weeks 4-7), and Phase 3 (Mitre-10 Cup - weeks 8-11; Semi-professional) over eleven weeks. The session rating of perceived exertion (sRPE) method was used to measure the players' internal training load (IL). Changes in IL were also interpreted using the acute chronic work ratio (ACWR). External training load (EL) metrics were assessed using GPS units. Players experienced sudden spikes in ACWR as they moved into Phase 3. Significant spikes with IL occurred at the start of each phase (weeks five and eight) with a large spike in ACWR occurring at week five (1.9 ±0.1). Players covered greater distances in Phase 3 at higher intensities, with a Total Distance (TD) of 16255 ±4576m, a High Speed Acceleration (HSA) count of 59 ± 32, and a High Speed Deceleration (HSD) count of 47 ± 19, following a similar trend of that observed with IL 3426 ± 368 (AU). The findings from this study show that players transitioning from an amateur to a semi-professional environment are vulnerable to sudden spikes in training load. Coaches from all levels should adopt a method of monitoring load and sharing the loading metrics. This would contribute to the planning of optimal TL for players who move into a semi-professional rugby environment.